The Relationship Between Nursing Service Activities and Nurses' Job Satisfaction - Rusyani, Herlin; Elinawati, Nurani Ai; Perceka, Andhika Lungguh; Huda, Taufik (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aimed to explore the correlation connection between nursing service activities and nurse job satisfaction at the Garut District Health Center, a government-run health facility responsible for various health efforts including promotion, prevention, and rehabilitation. The study utilized a quantitative approach employing a cross-sectional methodology, involving 92 informants selected through stratified random sampling. Data analysis involved employing the Spearman Rank test. The outcome indicated that 51.1% of informants (47 individuals) rated their nursing service activities positively, while 52.2% (48 individuals) expressed satisfaction with their work at the Puskesmas. The Spearman Rank test yielded a significant p-value of 0.002, indicating a correlation between nursing service activities and nurses job satisfaction at public health care the Garut. Consequently. It is recommended that the Puskesmas periodically conduct research or surveys on nurses' job satisfaction to serve as evaluative material for future organizational development and enhancement